2002
DOI: 10.1051/forest:2001009
|View full text |Cite
|
Sign up to set email alerts
|

Positive effect of drought on longicorn borer larval survivl and growth on eucalyptus trunks

Abstract: -Phoracantha semipunctata (F.) larvae attack and kill trees in Eucalyptus globulus (Labill.) plantations in Mediterranean countries. To test the hypothesis that these attacks are more likely in arid environments, we examined the effects of water deficits in the host trees of E. globulus on the mortality and growth of P. semipunctata larvae. Trees subjected to water stress during two subsequent years were compared with rainfed and irrigated trees. Larvae of P. semipunctata were artificially introduced in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Hodges and Lorio, 1969;Parker and Patton, 1975;Parker, 1979; reviewed by Mattson and Haack, 1987b;Thomas and Hodkinson, 1991;Caldeira et al, 2002;Tariq et al, 2012), with concomitant positive effects on insect development or survival (e.g. Thomas and Hodkinson, 1991;Caldeira et al, 2002;Tariq et al, 2012), it is difficult to extrapolate such effects to the scale of forest insect outbreaks (e.g. Larsson et al, 2000).…”
Section: Drought-stressed Trees May Be More Suitable For Insectsmentioning
confidence: 99%
“…Hodges and Lorio, 1969;Parker and Patton, 1975;Parker, 1979; reviewed by Mattson and Haack, 1987b;Thomas and Hodkinson, 1991;Caldeira et al, 2002;Tariq et al, 2012), with concomitant positive effects on insect development or survival (e.g. Thomas and Hodkinson, 1991;Caldeira et al, 2002;Tariq et al, 2012), it is difficult to extrapolate such effects to the scale of forest insect outbreaks (e.g. Larsson et al, 2000).…”
Section: Drought-stressed Trees May Be More Suitable For Insectsmentioning
confidence: 99%
“…Upon hatching, ELB larvae bore galleries along the phloem and cambium of trees, eventually preventing sap from flowing, which leads to rapid tree death during summer and fall [1,[4][5][6]. The ability of larvae to successfully colonize the host plant depends on low bark moisture content, leaving water-stressed trees particularly susceptible to attack by ELB [1,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the accumulation of osmolytes and soluble sugars in response to abiotic stresses may create favorable condition for biotic stress factors such as fungal pathogens and wood boring pests thereby increasing the susceptibility of trees. In support of this, Caldeira et al (2002) reported that a reduced bark moisture content and increased accumulation of glucose, fructose, and sucrose enhanced the survival and growth of Phoracantha semipunctata under drought conditions in E. globulus. Similarly, combined drought and pathogen infection increased soluble sugar concentration in Q. brantii (Ghanbary et al, 2018) resulting in increased susceptibility to pathogens (Ghanbary et al, 2017).…”
Section: Responses Of Forest Trees To Combined Biotic and Abiotic Strmentioning
confidence: 78%